2008
DOI: 10.1017/s174264640800126x
|View full text |Cite
|
Sign up to set email alerts
|

Hot beds of forensic psychiatry: Psychiatric intensive care units within medium security

Abstract: Aims: To conduct a survey investigating the provision of psychiatric intensive care within NHS medium secure units in England and Wales, gaining preliminary information about PICU size and clinical structure, and using this information to inform a discussion regarding PICU provision in medium security. Method: A postal survey was conducted.Results: A total of 30 MSUs were identified. The three groups of MSU differed significantly in size. Half of the MSUs surveyed either had a PICU or were developing one. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Some have suggested that the population cared for in medium security has changed over the years (Adams & Clark, 2008;Royal College of Psychiatrists, 2003;Mohan et al, 1997). There are a number of reasons why this might be.…”
Section: Methodsmentioning
confidence: 99%
“…Some have suggested that the population cared for in medium security has changed over the years (Adams & Clark, 2008;Royal College of Psychiatrists, 2003;Mohan et al, 1997). There are a number of reasons why this might be.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that PICUs are a rarity in forensic psychiatry but there is no published authoritative data. (20) In the past two decades, there have been significant developments in the standardised assessment of violence risk and management, including the introduction of 'structured professional judgement' approaches to risk assessment. The latter method is effectively an attempt to bridge the gap between clinical and actuarial approaches to risk assessment, by combining both elements into structured professional guidelines for clinical practice.…”
mentioning
confidence: 99%